2010
DOI: 10.1017/s0022029910000038
|View full text |Cite
|
Sign up to set email alerts
|

Effect of forage:concentrate ratio on the quality of ewe's milk, especially on milk fat globules characteristics and fatty acids composition

Abstract: The aim of this study was to evaluate the milk quality of Massese ewes receiving diets with different forage:concentrate ratios (FC ratio), specially on milk fat globules characteristics and fatty acids composition. The diet is one of the main environmental factors that influence the lipidic content of milk. A trial was carried out on twenty ewes, which had been subdivided into two homogeneous groups and kept indoors at 25 days post partum. The experiment lasted 60 days, from 40 to 100 days post partum and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
16
1
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 38 publications
(52 reference statements)
4
16
1
1
Order By: Relevance
“…In contrast, the fatty acids that ought to be reduced in the diet (particularly myristic and lauric acid) and the ratio of n-6/n-3 appeared to be closely associated with the supplementary feeding of both "hays" and "concentrate feeds", with the latter clearly being the most influential of all the factors considered. Again, this confirms indications from univariate analyses and previous studies [22,24,27].…”
Section: Possible Explanationssupporting
confidence: 90%
See 1 more Smart Citation
“…In contrast, the fatty acids that ought to be reduced in the diet (particularly myristic and lauric acid) and the ratio of n-6/n-3 appeared to be closely associated with the supplementary feeding of both "hays" and "concentrate feeds", with the latter clearly being the most influential of all the factors considered. Again, this confirms indications from univariate analyses and previous studies [22,24,27].…”
Section: Possible Explanationssupporting
confidence: 90%
“…The 21% increase and 9% increase, respectively, in the concentration of saturated lauric and (especially) myristic acid in milk from SI farms are also of concern, since these, along with palmitic acid, are the main SFAs linked to inflammation and increased cardiovascular risk, with the strongest connection being for myristic acid [12]. Such composition differences, along with the fact that ewes in the EX flocks produced 37% less milk, confirm previous studies that have reported that while higher conserved forage and concentrate feeds in dairy diets do increase productivity, they also have negative effects on milk's nutritional quality, especially in terms of FA profiles [24,27]. It ought to be noted here, however, that there were no differences in CLA or protein contents, the SCC, or CFUs, and there was only a small difference in the lactose content between milk from semi-intensive and extensive systems.…”
Section: Differences In Milk Yield and Compositionsupporting
confidence: 73%
“…Similarly, EPA and DHA content in the ewe's milk was increased by 18% and 67% respectively, by changing forage/ concentrate ratio from 40/60 to 60/40 (Martini, Liponi, & Salari, 2010). Grass feeding can increase also DHA content in beef (Scollan et al, 2006).…”
Section: Enrichment Of Foods With Epa and Dhamentioning
confidence: 81%
“…Each milk sample was thus characterised by a different percentage of MFGs, for each diameter size class. Subsequently, the ten classes were grouped, as reported in Martini et al (2010a), into three sizes of fat globules: small globules with a <2 µm diameter, medium-sized globules with a diameter from 2 to 5 µm, and large globules with a >5 µm diameter.…”
Section: Discussionmentioning
confidence: 99%